Pengujian User Experience Aplikasi Perangkat Bergerak Jagoan Indonesia Menggunakan Metode Usability Testing - Erlangga Rizki Pratama; Eriq Muhammad Adams Jonemaro; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Modernization requires all areas of human life to be fast and easy, including education. As is the case with activities to increase a sense of nationalism through learning Indonesian culture, carried out with methods that are creative, innovative, fun and not boring (Fadillah, 2016). Learning can use the application